Redox-Engineered Co―Cu―Zr Perovskites for Durable Anion Exchange Membrane Electrolysis - Natarajan, Logeshwaran; Nga, Ta Thi Thuy; Kwon, Minjae; Mannu, Pandian; Dong, Chung-Li; Lee, Sungho; Yoo, Dong Jin; Lee, Young Jun (Wiley - V C H Verlag GmbbH & Co., 2025)
The oxygen evolution reaction (OER) remains a critical bottleneck in water electrolysis and air-battery systems, requiring electrocatalysts with both high activity and long-term stability. Herein, Ba(ZrxCuyCo1-x-y)O3-δ (BZCC), a novel mixed-metal perovskite synthesized is introduced via a low-temperature hydrothermal method, which integrates multiple catalytic functionalities for efficient OER in alkaline media. The catalyst simultaneously activates the adsorbate evolution mechanism (AEM) and the lattice oxygen oxidation mechanism (LOM), driven by the redox flexibility of Co3+/Co4+. The incorporation of Cu2+/Cu3+ modulates the electronic structure to enhance intrinsic activity, while Zr4+ contributes to structural robustness against alkaline corrosion. The generation of oxygen vacancies (δ) through Cu/Co redox cycling, stabilized by Zr4+, facilitates OH− adsorption and promotes continuous O2 evolution. BZCC delivers a low overpotential of 238 mV at 10 mA cm−2 and demonstrates excellent durability, showing only a 116 mV increase in operating potential after 200 h. When applied in a single-cell anion exchange membrane water electrolyzer (AEMWE), the BZCC-based anode achieves a current density of 1.0 A cm−2 at 2.07 V, maintaining stable operation without performance degradation over 25 h. This combination of redox flexibility, electronic modulation, and structural stability positions BZCC as a scalable, high-performance electrocatalyst for sustainable AEMWE.